2007
DOI: 10.1002/jcb.21286
|View full text |Cite
|
Sign up to set email alerts
|

Ear mesenchymal stem cells (EMSC) can differentiate into spontaneously contracting muscle cells

Abstract: We have previously shown that cells isolated from the outer ears of adult mice are a source of mesenchymal stem cells that can be induced to differentiate into adipo-, osteo-, and chondrocytes. In this study, we demonstrate that ear mesenchymal stem cells (EMSC) express stromal cell-associated markers (CD44, CD73) and stem cell marker Sca-1 and can be differentiated into spontaneously contracting muscle cells. Treatment of cells with epidermal growth factor (EGF) change their morphology from fibroblast shapes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 71 publications
2
26
0
Order By: Relevance
“…mice showed similar in vitro differentiation potentials, suggesting that EMSCs are necessary but not suffi cient for the regeneration in ear punched model [12]. Immunophenotype analysis of the cells [13] revealed that EMSCs are positive for stem cell (stem cell antigen-1; Sca-1) and stromal markers (CD90, CD73, CD44), but negative for hematopoietic markers (CD45, CD4); however, the study was limited only to cells cultured at passage 0. The present study was undertaken to extend the characteristics of EMSCs.…”
Section: Colony-forming Unit (Cfu) Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…mice showed similar in vitro differentiation potentials, suggesting that EMSCs are necessary but not suffi cient for the regeneration in ear punched model [12]. Immunophenotype analysis of the cells [13] revealed that EMSCs are positive for stem cell (stem cell antigen-1; Sca-1) and stromal markers (CD90, CD73, CD44), but negative for hematopoietic markers (CD45, CD4); however, the study was limited only to cells cultured at passage 0. The present study was undertaken to extend the characteristics of EMSCs.…”
Section: Colony-forming Unit (Cfu) Assaysmentioning
confidence: 99%
“…Previous studies in our laboratory showed that both the external murine ears [12] and ear punches obtained during standard procedure used for marking live animals [13] are a source of MSCs. Termed ear mesenchymal stem cells (EMSCs), these cells have the characteristics of stem cells including the ability to self-renew and to commit into adipocyte, osteocyte, chondrocyte, and myocyte lineages at the clonal level [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Red blood cell lysis buffer (Sigma Co., St. Louis, MO) was used to remove erythrocyte contamination before analyzing by flow cytometry. Cells isolated from the fat depots were incubated with phycoerythrin-conjugated antiSca-1, antiCD44, antiCD45, antiCD73, antiCD90.1, antiCD-90.2, and antiCD117 antibodies (BD Pharmingen, San Diego, CA), as previously described [17]. The flow cytometry assay was performed using a FACScan flow cytometer (Becton Dickinson, San Jose, CA) and data were analyzed with a Macintosh G5 workstation (Apple Computer, Cupertino, CA), which contains Cellquest graphics software (Becton Dickinson) for data acquisition and analysis.…”
Section: Flow Cytometry Assaymentioning
confidence: 99%
“…Ear mesenchymal stem cells (EMSC) were first isolated as a primary culture from the external ear tissue of adult mice and shown to possess the capacity for selfrenewal and differentiation into chondrocytes, osteocytes, adipocytes [18] and myocytes [19]. EMSC also serve as a simple model for adipogenesis [20] with potentially broader applications for regenerative medicine [21].…”
Section: Introductionmentioning
confidence: 99%